STRATEGI MANAJEMEN KOLABORATIF PERANGKAT DAN PKK DESA BERBASIS INDEK DESA MEMBANGUN (IDM) BERKEMBANG - Ahya, Rahmatul; Iwan Ristanto; Agung Wibawa, Satria; Sri Lestari, Mathilda (Inisiasi, 2025)
This study aims to analyze the collaborative management strategy between village officials and PKK (Family Welfare Movement) cadres in enhancing the village’s economic resilience based on the Village Development Index (IDM) in Sendangagung Village, Giriwoyo Subdistrict, Wonogiri Regency. The research employed a qualitative approach with a case study design, supported by quantitative data from two training programs: an Android-based application training for preparing rural road budget plans (RAB), and dish soap production training for PKK cadres. The findings reveal that the collaborative strategy between village officials and PKK was implemented through participatory planning, integrated execution, and utilization of local resources and appropriate technology. Quantitatively, village officials (N=12) demonstrated an average RAB preparation time of 2.2 minutes using the application, with all participants mastering the basic functions. Meanwhile, PKK cadres (N=15) experienced an average knowledge score increase of 37.7 points, and 40% expressed interest in producing dish soap independently. This collaborative strategy has proven effective in strengthening the community’s social and economic resilience dimensions and contributes to improving the village’s IDM status.